Word Bank: Learning Media on Poetry Writing Materials for Fourth Grade of Elementary School - Alfianita Ayu Larasati; Ali Mustadi (Universitas Pendidikan Ganesha, 2024)
Students benefit from writing poetry because they can express their feelings at the time through beautiful words in the form of poetry. Writing poetry in learning can be packaged using learning media. Learning media is extremely beneficial to the learning process. Students will understand the material provided by the teacher more easily if they use learning media. Therefore, this research aims to produce the learning media product